Soldering wire at Hercules Port Ewen plant - Hercules Incorporated (1954)
Close-up view of employee Mildred Best soldering platinum bridge wires across the two ends of the lead wires used in the electric blasting caps manufactured at the Hercules Powder Company plant in Port Ewen, New York. During the production of electric blasting caps, wires were inserted into the base of a bridging machine while a mixture of sulfur, graphite, and mica was poured in a mold to form a plug around the so-called leg wires. Then, a platinum alloy bridge wire was soldered across the two ends of wire protruding from the plug. Following inspection, the plugs subsequently were sent to the Filling Room to be inserted into shells. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) specialized in the manufacture of explosives and smokeless powders. The company's Port Ewen plant produced a range of special detonators designed for military use, as well as construction jobs that required blasts of dynamite, such as the clearing of quarries, mines, and tunnels.
Keywords: Detonators; Chemical industry; Solder and soldering; Propellants; Hercules Incorporated; Corporations; Explosives